Sistematic Literature Review (SLR): Pembentukan Karakter Berakhlak Mulia Pada Generasi Alfa Melalui Program 7 Kebiasaan Anak Indonesia Hebat - Veriani, Eva; Tutik Wijayanti; Agung Try Prasetya; Decky Avrilianda (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to assess the contribution of the 7 Habits of Great Indonesian Children program in shaping the noble character of the Alpha generation in elementary schools. This study uses a Systematic Literature Review (SLR) approach to collect data by examining 10 national scientific articles published between 2022 and 2026. The analysis was conducted to identify and evaluate various empirical and theoretical findings regarding the implementation of the 7 Habits of Great Indonesian Children program both in the school environment and the family environment. The results of the study indicate that the habits of Waking Up Early, Worshiping, Exercising, Eating Healthy and Nutritious Foods, Enjoying Learning, Being Social, and Sleeping Early in the 7 Habits of Great Indonesian Children program play a positive role in shaping the noble character of the Alpha generation. The success of the program is supported by good collaboration between teachers and parents as well as a conducive school environment and consistent implementation of this program. The challenge faced by this program in shaping noble character is the lack of parental supervision of students' gadget use at home.